Knowledge as a Basic Development Factor of Industry and Services - Brzozowski, Tomasz Tadeusz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
The subject of this article is knowledge as a basic instrument, which can be applied in industryand services. Currently, a status of this kind of knowledge is changeable and most frequently it isconnected with pragmatic dimension of contemporary business. At present it seems that the ancient andmedieval idea of disinterested knowledge belongs to the past.The main aim of this paper is an attempt to redefine the real meaning of knowledge in modern timesand to establish what impact business sphere has on social relationships. Changes which occur in wayswe relate to each other, in my mind, are a result of expansionist and attractive world of economy for thecontemporary human being.Nowadays, the pragmatic knowledge narrows them only to the instrument of increasing profit andbuilding competitive advantage in business. The most important and visible changes in the meaning andfunction of knowledge occur in industry and service sectors.